Common response of dominant plants in typical grassland of Inner Mongolia to long‐term overgrazing revealed by transcriptome analysis. (27th July 2021) - Wan, Dongli; Wan, Yongqing; Ren, Weibo; Yu, Linqing; Ding, Yong; Li, Guojing; Li, Fang; Hou, Xiangyang
Abstract: Leymus chinensis (Trin.) Tzvel. and Stipa grandis P. Smirn. are dominant species in grassland on the typical steppe of Inner Mongolia. Long‐term overgrazing, which is considered to represent multiple stresses, reduces the growth of L. chinensis and S. grandis . To gain an understanding of the molecular mechanisms underlying the responses of these plants to overgrazing, we explored the gene expression profiles of L. chinensis and S. grandis to discover the common features of these dominant plants in response to overgrazing. Using the Illumina RNA‐Seq platform, two sequencing libraries prepared from non‐grazed (Lc‐NG) and overgrazed samples (Lc‐OG) of L. chinensis were sequenced. Using Trinity software assembly, 129, 087 unigenes with a mean length of 693 bp and an N50 of 1, 093 bp were obtained by combining the Lc‐NG and Lc‐OG data. By comparing differentially expressed genes (DEGs) of L. chinensis with those of S. grandis, we identified 16 Kyoto Encyclopedia of Genes and Genomes pathways and 15 Gene Ontology terms that were significantly enriched with DEGs in both species. Most of these DEG‐enriched pathways, for example, phenylpropanoid biosynthesis and flavonoid biosynthesis, were related to stress responses. The results suggest that stress plays an important role in plants' responsiveness to long‐term overgrazing and associated reductions in plant growth. The DEGs shared by these two species will be valuable for further research on key genes and molecular mechanisms involved in plants' adaptation to overgrazing and associated stresses.